2016
DOI: 10.3109/0886022x.2016.1138832
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of mercury vapor can cause the toxic effects on rat kidney

Abstract: Dental amalgam has been used in dentistry as a filling material. The filler comprises mercury (Hg). It is considered one of the most important and widespread environmental pollutants, which poses a serious potential threat for the humans and animals. However, mercury deposition affects the nervous, cardiovascular, pulmonary, gastrointestinal, and especially renal systems. In most animals' species and humans, the kidney is one of the main sites of deposition of mercury and target organ for its toxicity. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The chronic exposure to mercury takes the oxidative stress, metallothionein induction and organ toxicity in rats (Agrawal et al, 2014 ). The effects of chronic mercury exposure were on the lysosome system and oxidative stress on the rat kidney (Hendriksen et al, 2007 ; Akgul et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The chronic exposure to mercury takes the oxidative stress, metallothionein induction and organ toxicity in rats (Agrawal et al, 2014 ). The effects of chronic mercury exposure were on the lysosome system and oxidative stress on the rat kidney (Hendriksen et al, 2007 ; Akgul et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic mercury vapor exposure can cause renal injury. Investigation of kidney tissues of Wistar rats exposed to 1 mg/m 3 Hg vapor per day revealed histological alteration of the kidneys after 45 days (Akgül et al, 2016). However, the renal Hg deposition might be slow by the inhibition of γ-glutamyltranspeptidase, resulting in increased urinary Hg concentration.…”
Section: Animal Studiesmentioning
confidence: 99%
“…The organ specific toxicity of mercury exposure has been described in animal studies before [ 64 , 65 , 66 ]. Akgül and colleagues showed that exposure to mercury vapour caused histological renal damage in rats [ 64 ].…”
Section: Discussionmentioning
confidence: 99%